Investigation of Attitudes and Behaviors Towards Recycling with Theory Planned Behavior - Veysel Yılmaz; Erkan Arı (Journal of Economy Culture and Society)
Recycling is defined as the re-inclusion of wastes that can be reused in the production process by undergoing various processes. At the same time, recycling is seen as the most important environmental behavior that reduces the amount of solid waste and conserves resources. Considering the importance of recycling for a sustainable future, it is of great importance to determine the factors affecting the recycling behavior of individuals. Due to the rapid increase in environmental problems and their extremely negative impact on life, it is necessary to determine the environmental and recycling behaviors of individuals and produce solutions. In this study, attitudes and behaviors towards recycling were investigated with the help of a model proposed within the scope of Theory Planned Behavior (TPB). The analysis of the data was made using the Partial Least Squares Structural Equation Modeling (PLSSEM) Smart-PLS software, which can be used successfully in small-volume samples and does not require the assumption of multivariate normality. It was determined because of PLS-SEM fit criteria that TPB is suitable for explaining recycling attitudes and behaviors. As a result of the analysis, it was revealed that attitude, subjective norm, and perceived behavioral control positively and significantly affect recycling intentions.